Analysis of Tourism in the Slovak Republic in the Period after Accession to the European Monetary Union - FIĽARSKÁ, Jana; VOZÁROVÁ, Ivana KRAVČÁKOVÁ; KOTULIČ, Rastislav (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017DO - 10.14505//jemt.v8.6(22).01, 2018)
Tourism is an important part of the economy in the world. Despite good conditions in Slovakia, the share of tourism in the economy accounts for only a small percentage. The rise in tourism would greatly benefit especially for the growth of employment rate, wage growth, the influx of foreign tourists and ultimately would particularly benefit the growth of Slovakia's economy. The aim of this paper was to describe tourism and selected indicators of tourism and their impact on employment, added value and wages of employees. Slovakia has many natural beauties, cultural and historical sights, so these advantages should be used to develop the economy. In the paper was used method of analysis of selected indicators of tourism. The indicators were examined and subsequently compared during the period from 2009 to 2015. Meaning of analysis of indicators has a direct impact on the growth of employment in Slovakia, the improvement of the services provided and the indirect impact on the growth of other products for the development of tourism. Slovakia has a high potential in terms of tourism but needs to be more visible, especially abroad, needs to offer more educated workers in the field, promote the growth of wages and bonuses and overall to support entrepreneurship in tourism.